The changing association between marriage, work, and child poverty in the US: 1974-2010 - Regina S. Baker (Luxembourg Income Study (LIS), 2015)
Marriage and work have long been central to debates regarding poverty and the family. Although ample research demonstrate their negative association with child poverty, both marriage and work have undergone major transformations over recent decades. Consequently, it is plausible that their association with child poverty may have also changed. Using ten waves of U.S. Census Current Population Survey data from the Luxembourg Income Study, this study examined the relationships between marriage, work, and relative measures of child poverty from 1974-2010. Results indicated both marriage and work still decrease the odds of child poverty. However, time interactions showed marriage's negative association with child poverty has declined in magnitude, whereas work's negative association with child poverty has increased in magnitude. These findings underscore the historically-varying influence of demographic characteristics for poverty. They also suggest the limitations of overemphasizing marriage and the growing importance of work for reducing child poverty in America.
Keywords: 330